miR-3529-3p/ABCA1 axis regulates smooth muscle cell homeostasis by enhancing inflammation via JAK2/STAT3 pathway - Wang, Tingyu; Yu, You; Ding, Yinglong; Yang, Ziying; Jiang, Shumin; Gao, Faxiong; Liu, Shan; Shao, Lianbo; Shen, Zhenya (Frontiers in Cardiovascular Medicine, 2024)
Background Thoracic Aortic Dissection (TAD) is a life-threatening disease without effective drug treatments. The disruption of HASMCs homeostasis is one direct histopathologic alteration in TAD pathological process. Several miRNAs have been shown abnormally expressed in TAD and to regulate HASMCs homeostasis. The primary goal of this study is to identify the miRNAs and the specific mechanisms that lead to HASMCs homeostasis disruption. Methods Bulk miRNA sequencing was performed to explore the aberrantly expressed miRNA profile in TAD, and differentially expressed miRNAs were verified with qRT-PCR. To explore the role of the key miRNAs (miR-3529) in HASMCs homeostasis, we overexpressed this miRNA with lentivirus in HASMCs. Integrative transcriptomics and metabolomics analysis were used to uncover the functional roles of this miRNA in regulating HASMCs homeostasis. Further, the target gene of miR-3529 was predicted by bioinformatics and verified through a dual-luciferase reporter assay. Results Bulk miRNA sequencing showed miR-3529 was elevated in TAD tissues and confirmed by qRT-PCR. Further experimental assay revealed miR-3529 upregulation induced HASMCs homeostasis disruption, accompanied by reducing contractile markers and increasing pro-inflammatory cytokines. Integrative transcriptomics and metabolomics analysis showed that miR-3529 overexpression altered the metabolic profile of HASMC, particularly lipid metabolism. ABCA1 was found to be a direct target of miR-3529. Mechanistically, the miR-3529/ABCA1 axis disrupted HASMCs homeostasis through the JAK2/STAT3 signaling pathway. Conclusions miR-3529 is elevated in TAD patients and disrupts HASMCs homeostasis by reprogramming metabolism through the JAK2/STAT3 signaling pathway. These findings favor a role for miR-3529 as a novel target for TAD therapy.